Beyond Glucose: Empagliflozin’s Impact on Fatty Liver in Patients with Type 2 Diabetes; A True Game Changer (Indus Journal of Bioscience Research, 2025)
Background: Type 2 Diabetes develops in adulthood, and is caused due to failure of pancreatic B-cells to secrete insulin, gradually causing desensitization of B-cells to glucose, leading to insulin resistance1-5. According to American Diabetes Association, due to the chronicity of this disease, long-term complications arise which mostly occur due to hyperglycemia causing microvascular and macrovascular damage6. This brings about significant damage to the heart, eyes(retinopathy), kidneys (chronic kidney disease) and nerves(neuropathy).5 Metabolic dysfunction-associated fatty liver disease (MAFLD) previously known as non-alcoholic fatty liver disease (NAFLD), is defined inclusively as presence of fatty liver disease associated with presence of obesity or Type 2 Diabetes mellitus (T2DM). Objectives: To determine the efficacy of Empagliflozin on liver fat content in type 2 diabetics and metabolic dysfunction associated fatty liver disease. Methodology: In this Observational study, 200 patients were enrolled via Non-Probability Convenient sampling.  It was conducted at Department of Endocrinology Fatima Memorial Hospital, Lahore from 12th October 2024 to 11 January 2025. Results: There were total of 200 patients who were enrolled and 114(57%) were males and 86(43%) patients were female. The mean age of the participant was 44.6±6 years. Empagliflozin led to a significant 12.07%± 2.86% reduction on USG. Empagliflozin after three months showed a significant ALT reduction to 28 IU/L from 38 IU/L, showing remarkable results. (p-value